Zn and Mn impurity effect on electron and luminescent properties of porous silicon - Primachenko, V.E; Kirillova, S.I.; Manoilov, E.G.; Kizyak, I.M.; Bulakh, B.M.; Chernobai, V.A.; Venger, E.F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
Investigated in this work are por-Si/n-Si structures prepared by anodizing silicon in 1 % HF water solution, which was followed by natural aging in air and doping with Zn and Mn impurities. When aging, the oxide film of nanoelements in the above structures is substituted by a silicate one. Measurements of temperature dependencies (100...300 K) describing the capacitance photovoltage behavior caused by intense pulses (∼10²¹ quanta/cm2s) of red or white light enabled us to determine the following values and their changes: the boundary potential for n-Si, distribution of the concentration inherent to boundary electron states in the n-Si forbidden gap, concentration of traps for non-equilibrium holes at the interface por-Si/n-Si and in the por-Si layer. The substitution of the oxide film by the silicate one, the thickness of which can exceed the initial thickness of the oxide film, makes these structures more stable and results in sizable changes of spectral dependencies of the short-time (t < 250 ns) and integrated (t > 250 ns) photoluminescence relaxation components as well as shifts the latter into the shortwave range.